Analisis Tingkat Kesehatan Koperasi Simpan Pinjam Desa Bondalem Tahun Buku 2021 - Sudarsana, Kadek Agus; Yuniarta , Gede Adi (Jurnal Ilmiah Akuntansi dan Humanika, 2022)
This study describes the health level of KSP which is located in Bondalem Village for Financial Year 2021. The health level of a cooperative is the state of a cooperative seen from various aspects used by cooperatives in running their business in one period. \The data collection methods used are three methods including the observation method, the interview method, and the documentation method. Sources of data and types of data used are primary data and secondary data. The results of the research that the authors have obtained show the level of health of KSP in the three cooperatives in Bondalem Village for the fiscal year 2021. KSP Cipta Mulia and KSP Usaha Beraya Bopeas each received the predicate quite healthy, because the value obtained lies in the range of 66.00≤x <80.00. KSP Cipta Mulia got a final score of 68.60 and KSP Usaha Beraya Bopeas got a score of 79.85. Meanwhile, the health level of the Sapta Sedana Murti Savings and Loans Cooperative is classified as Under Supervision because the final score obtained is in the range of scores of 51.00 < x < 66.00. KSP Sapta Sedana Murti got a score of 53.65. Meanwhile, if the average score obtained from the three savings and loan cooperatives located in Bondalem Village obtained a score of 67.36 which is classified as quite healthy.